THE USE OF PROBIOTICS IN FEED ON THE PERFORMANCE OF KAMPUNG UNGGUL BALITBANGTAN (KUB) CHIKENS IN THE STARTER PHASE (A CASE STUDY) - Sam Saputra; Youdhie H. S. Kowel; Florencia Nery Sompie; Betty Bagau (Jambura Journal of Animal Science, 2026)
This study aimed to evaluate the effect of probiotic supplementation in feed on the performance of Kampung Unggul Balitbangtan (KUB) chickens during the starter phase. The research was conducted at Tokatindung Reference Integrated Ecofarming Development (TRIED) Farm of PT MSM–TTN, Pinenek Village, East Likupang District, North Minahasa Regency, over a four-week rearing period. A total of 100 day-old KUB chickens were used in this study. Variables including feed intake, body weight gain, and feed conversion ratio. Liquid probiotics are administered through feed at a level of 2% v/w. Data were using Microsoft Excel. The results showed that the average feed intake of KUB chickens was 23 ± 13.52 g/bird/day, body weight gain was 12.12 ± 0.57 g/bird/day, and the feed conversion ratio was 1.89. These values are still within the standard performance range of KUB chickens in the starter phase, so it can be concluded that the use of probiotics in feed in this study has not had an effect on improving the performance of KUB chickens in the starter phase.